Sport and type 1 diabetes - a great value but also a challenge. Review of the literature and guidelines - Błaszczak, Karolina; Kruszewski, Adrian; Paduszyńska, Natalia; Dąbrowska, Anna; Przybysz, Paulina; Szyszka, Monika; Kucharska, Maja (Quality in Sport, 2024)
Introduction: Type 1 diabetes is a disease requiring complex treatment: intensive functional insulin therapy with multiple subcutaneous insulin injections (Multiple daily doses of insulin- MDI) or continuous subcutaneous insulin infusion (CSII) with a personal insulin pump. Type 1 diabetes is a disease with many complications including cardiovascular diseases. A key element in good disease control is adequate patient education. This paper will focus on physical activity and its impact on the course of the disease. Aim of the study: To research the impact of physical activity on the course of type 1 diabetes. To reinforce medical professionals’ knowledge of exercise management among patients with type 1 diabetes. State of Knowledge: Regular physical exercise is beneficial for diabetes control, at the same time reducing the need for insulin. It also reduces the risk of dangerous late cardiovascular complications. Meta-analyses have shown a significant effect of physical activity on the reduction of HbA1c, BMI, triglycerides and total cholesterol. Continuous glucose monitoring (CGM) systems are recommended for physically active people with type 1 diabetes. Optimal glycaemia at the start and during sport are: for aerobic exercise 126-180 mg/dl (7-10 mmol/l), for anaerobic exercise 90-180 mg/dl (5-10 mmol/l). The reduction in insulin dose depends on the type of exercise, the length of the exercise, the method of treatment, and the pre-exercise blood glucose level. Conclusion: Physical exercise improves the control of type 1 diabetes and therefore reduces the risk of complications of the disease including cardiovascular diseases. Type 1 diabetes is not a contraindication to both amateur and professional sport. However, many variables need to be considered. Every patient with type 1 diabetes must be properly trained before starting exercise.